Pattern and management outcomes of head and neck hemangiomas: a prospective study from Tanzania - Mungia Abbas M.; Owibingire Sira Stanslaus; Moshy Jeremiah Robert; Sohal Karpal Singh; Sianga William (EDP Sciences, 2021)
Introduction: Hemangiomas arise from the proliferation of endothelial cells surrounding blood-filled cavities. They have a slightly higher female predilection and about 60-70% of them occur in the head and neck region. Various medical and surgical options are available for the treatment of hemangiomas. Aim: To determine the pattern and management outcomes of head and neck hemangiomas in Tanzania. Material and methods: This was a one-year prospective, cross-sectional study that involved all consecutive patients with head and neck hemangiomas treated in Muhimbili National Hospital. A structured questionnaire was used to collect information including age and sex of the patient, chief complaint and, duration, size and site of the lesion. The treatment modalities were surgery and/or intralesional bleomycin injection (IL-Bleo). A standard dose of bleomycin was 0.3 to 0.6 mg/kg per injection not exceeding 15 units per cycle with a maximum of 6 cycles. Frequency distribution and cross-tabulation were performed and association between variables was assessed by the Chi-square test, whereby the p-value was set at p < 0.05. Results: A total of 58 patients were included in the study. The male to female ratio was 1:1.4 and the median age was 6.15 years. Majority (74%) of the patients had infantile hemangioma. The most common presenting complaint of patients/guardians of the patients were facial disfigurement (94.8%), pain (32.8%) and ulceration (22.4%). The most frequently involved sites were the lips (55.2%) followed by the cheeks (37.9%). In patient who were managed surgically, there was a 100% reduction in size of the lesion. Of those who were treated with bleomycin, the percentage reduction in the area of the lesion ranged from 8.33% to 100% with mean of 72.6%. Only 6% of the patient had post IL-Bleo complications. Conclusion: Head and Neck hemangiomas are more common in females and majority are infantile hemangioma. Facial disfigurement is the commonest presenting complication of these lesions, and the lips and the cheeks are mostly affected areas. Intralesional bleomycin is an effective treatment modality which has low complication rates.